Fabrication of a pressure gauge for the mosquito artery clamp based on the LJ12A3-4-Z / BX proximity sensor - Novella Febriana; Yulkifli Yulkifli; Ratnawulan Ratnawulan (PILLAR OF PHYSICS, 2017)
This research aims to design and develop a pressure gauge on the mosquito arterial clamp based on LJ12A3-4-Z/BX proximity sensor and to determine the performance specifications and proximity sensor-based equipment specifications LJ12A3-4-Z / BX. This study was  engineering. The data collection done by measured the direct and indirect measurement.. Direct measurements carried out on proximity sensor output npn type LJ12A3-Z / BX, while indirect measurements carried out to determine the accuracy and precision of the instrument pressure gauge. The data obtained through the measurement was analyzed in two ways, namely by statistics and graphs. Based on data analysis that has been done can be put forward three important results. First, spesification of  system performance pressure gauges at the arterial clamp LJ12A3 proximity sensor-based mosquito-Z / BX consists of a mosquito artery clamps connected by a proximity sensor type LJ12A3 npn-Z / BX and a box. Second, used to process the input data and processing data of sensor measurement data by the Arduino Uno microcontroller was. Third, this sensor has a sensor that outputs a value inversely proportional to the frequency of the pressure on the clamps are used, with the slope of 0.386. Meanwhile, the coefficient of determination obtained a straight line approach around 0.876. The resulting clamping pressure is inversely proportional to the value of the slope of the graph of No - 1,074. Through with the near of  straight line coefficient of determination of the chart of 0726